Immune Checkpoint Inhibitor Use in Microscopic Colitis - Natalie Farha; Joseph Sleiman; Pauline Funchain; Jessica Philpott (Annals of Internal Medicine: Clinical Cases)
Immune checkpoint inhibitors (ICIs) are a novel class of anticancer therapies that can result in autoimmune pathology known as immune-related adverse events (irAEs). Because of the risk for irAEs, patients with preexisting autoimmune diseases have been excluded from safety trials for ICIs. Although the pathophysiology of microscopic colitis is not fully understood, it is considered part of the spectrum of immune-mediated gastrointestinal diseases. Little is known about the effects of ICIs on patients with microscopic colitis. This case series describes 4 patients with microscopic colitis requiring ICIs for cancer therapy and gastrointestinal-related outcomes after ICI therapy.